The Achuar People of the Corrientes Basin: The State vis a vis its own Paradigm - Chirif, Alberto (2010)
The paper analyses the events leading to the 2006 uprising of theAchuar people of the Corrientes basin (Loreto), who have sufferedfour decades of contamination due to oil exploitation. It also examinesthe Peruvian State’s and the oil company´s attitudes throughoutthe protest and after signing an agreement aiming to stop contaminationand remedy environmental and social havoc. Materials usedinclude interviews conducted with different stake holders and a widerange of written records, such as political declarations, reports onlocal people´s health´s and remediation work, agreement documentsand letters exchanged between stake holders, as well as historicaland socio economic background information. Findings highlight thestrength of organized indigenous people´s claiming for their rights;the greater commitment to assuming responsibility shown by the oilcompany´s as compared to the Peruvian State; and the weakness ofa political discourse equating development with the extraction ofnatural resources. The main conclusion is that the Peruvian Statedoes not fulfill the paradigm set in the first article of the Constitution:that the defense of the human person and the respect of its dignityare its supreme aim.